Journey to the center of the earth - Verne, Jules, 1828-1905.; Project Gutenberg (Salt Lake City : Project Gutenberg Literary Archive Foundation, 2006)
A German professor, his nephew, and their guide explore a volcanic crater in Iceland that leads them to the center of the Earth and to incredible and horrifying discoveries.
Human-read audiobook.
Mode of access: World Wide Web.
Keywords: Explorers -- Fiction; Science fiction; Audiobooks